Teaching profession: A study of career abandonment in contemporary (Research, Society and Development, 2019)
The objective of this study was to investigate the factors that influence teachers in the contemporary context to the abandonment of the teaching career. The research carried out is of the bibliographic type, with a qualitative character. Data collection was carried out in the following electronic databases: Scielo, Google Scholar, Bireme, repositories of dissertations and theses of the main Brazilian universities during the second half of 2018. The results of the study indicate that the lack of appreciation of the teacher, the precarious conditions of work, low wages, lack of incentive for initial and continuing training, disrespect, and overwork lead to exhaustion, disenchantment and frustration and consequently dropping the teaching career.